Letter - Muggeridge, Eric G.
012a-0020-001 Foster Parents' Plan for Children In Spain AMERICAN HEADQUARTERS HOTEL BEDFORD 118 EAST 40th STREET NEW YORK, N.Y. CALEDONIA 5-1000 ERIC G. MUGGERIDGE, Secretary BRITISH HEADQUARTERS 135 HARLEY STREET LONDON W.1. JOHN LANGDON-DAVIES, Chairman Partial list of British sponsors The Duchess of Atholl The Earl of Listowel Viscount Cecil of Chelwood D. R. Grenfell, M.P. Lawrence Housman [ ] R J Macnamara Eleanor Rathbone. M.P. Wilfrid Roberts, M.P. Stephen Spender PARTIAL LIST OF AMERICAN SPONSORS CARLETON BEALS STEPHEN V. BENET WILLIAM R. BENET ALGERNON D. BLACK ELEANOR CARROLL CHILTON FLOYD DELL PROF. and MRS. PAUL DOUGLAS EDDIE DOWLING FRANCES FARMER HELEN HALL HELEN HAYES LILLIAN HELLMAN DR. JOHN HAYNES HOLMES JOSEPHINE JOHNSON MRS. H.V. KALTERNBORN HELEN KELLER MANUEL KOMROFF ARCHIBALD MACLEISH THOMAS MANN [ ] L. MAYER ROBERT NATHAN KATHLEEN NORRIS DOROTHY PARKER CHANNING POLLOCK LUIS QUINTANILLA WILL ROGERS JR. MRS JAMES ROOSEVELT VIDA D. SCUDDER GEORGE AND HELEN SELDES BOOTH TARKINGTON LOUIS UNTERMEYER PROF. and MRS HAROLD C. UREY MISS LILLIAN D. WALD JOHN HALL WHEELOCK PERCIVAL WILDE THORNTON WILDER MRS. STEPHEN S. WISE DR. MARY E. WOOLLEY AMERICAN TREASURER DAVID J. ALGASE, C.P.A. November 6th, 1938 Sir Walter Citrine Trade Union Congress, Transport House Westminster S.W.1 London, England Dear Sir Walter: It is just possible you may have heard of the various tasks I was able to carry through during the time I was in Spain for the National Joint Committee. I certainly found everything in that country to encourage me morally and politically. When John Langdon-Davies left for America, I preceeded him by a short time in order to carry through the preliminary negotiations for creating an organization in this country for his Foster Parents Plan. We successfully carried through this task. On his departure I was appointed executive secretary of the organization to continue the work and aid in the general collection of relief funds. The adoption plan went over very well indeed, as it was something new in this country. With the cooperation of the North American Committee I was able to spend each and every evening speaking before meetings. In all, I attended some two hundred and fifty to three hundred meetings. Some times speaking about the need for help and other times giving an educational outline of what the Spanish fight really means. I am returning to England on the "Aurania" Cunard White Star Line, which leaves New York on December 8th and arrives at London Dock on December 19th. I am writing to you in the hope that you may have some work for me to do for Spain in any capacity whatsoever. Spain and America's reaction to the Czechoslavakian crisis, are certainly grouped together in such a way as to be especially significant towards our present day problems. I hope I shall be able to see you upon my return. I have also written to Mr.Harris about my return. Trusting, you are completely well, and with many happy memories, Sincerely yours, Eric EM/eb 292/946/12a/20